Pediatrics : PreTest self-assessment and review /;[edited by] Robert J. Yetman, Mark D. Hormann. - Hormann, Mark.; Yetman, Robert (New York : McGraw-Hill Medical, 2013)
The closest you can get to seeing the USMLE Step 2 CK without actually taking it Pediatrics: PreTest Self-Assessment & Review is the perfect way to assess your knowledge of pediatrics for the USMLE Step 2 CK and shelf exams. You'll find 500 USMLE-style questions and answers that address the clerkship's core competencies along with detailed explanations of both correct and incorrect answers. All questions have been reviewed by students who recently passed the boards and completed their clerkship to ensure they match the style and difficulty level of the exam. 500 USMLE-style questions and answers Detailed explanations for right and wrong answers Targets what you really need to know for exam success Student tested and reviewed--Provided by publisher.
General pediatrics -- The newborn infant -- The cardiovascular system -- The respiratory system -- The gastrointestinal tract -- The urinary tract -- The neuromuscular system -- Infectious diseases and immunology -- Hematologic and neoplastic diseases -- Endocrine, metabolic, and genetic disorders -- The adolescent.
Includes bibliographical references and index.
Keywords: Pediatrics